The Privatisation of State Education - Fu, Lihan (Journal of Theory and Practice of Contemporary Education, 2023)
This article analyses the privatisation of education. The causes and processes of the emergence of privatisation of education are explored in terms of both exogenous and endogenous educational policies. The benefits and disadvantages of privatisation of education are described separately, using the academisation of schools in the UK and shadow education in South Korea as case studies.